Urban Visualization: User Centered Mapping. - Wessel, Ginette.; Chang, Remco.; Sauda, Eric. (Tufts University. Tisch Library., 2017)
The complexity of contemporary urban environments demands new mapping techniques that combine information and urban geometry in a manner that responds to our cognitive processes. Working directly with cognitive scientists, computer scientists, and architects, the Urban Visualization Group at UNC Charlotte has been investigating new ways to visualize the city as it relates to our mental representations. Our research has investigated theories of urban legibility and summarized possible conceptual approaches to urban form. Through cognitive experiments involving 80 subjects, we have developed semantic and mental depictions (from sketch maps) from which we were able to infer perceptions of the city. Based on this research, we developed a set of design principles that can serve as the basis for feasible alternatives of urban visualization. We have selected usercentered mapping as the next focus of our work.